Method for producing liquid crystal polymer separator and liquid crystal polymer separator

By introducing fillers into the liquid crystal polymer separator to construct a porous structure, the problem of excessive barrier properties of the liquid crystal polymer film is solved, and the ionic conductivity and mechanical strength are improved, making it suitable for battery separator applications.

CN122118292APending Publication Date: 2026-05-29SHENZHEN SUNWAY COMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610273112.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-06
Publication Date
2026-05-29

AI Technical Summary

Technical Problem

Existing liquid crystal polymer (LCP) films have excessively strong barrier properties, making it difficult to form a porous structure. This hinders the effective conduction of electrolyte ions, limiting their application in the field of battery separators.

Method used

By adding fillers such as paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micro powder, silica micro powder, sodium bicarbonate micro powder, and starch micro powder during the preparation of liquid crystal polymer separators, and utilizing the occupancy of the fillers in the wet film and subsequent removal, an interconnected or independently distributed porous structure is constructed in the liquid crystal polymer matrix, thereby increasing the porosity.

Benefits of technology

The ionic conductivity of the liquid crystal polymer separator is enhanced while maintaining good mechanical properties and structural integrity, reducing the occurrence of damage during battery assembly and charging/discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122118292A_ABST
    Figure CN122118292A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a liquid crystal polymer diaphragm and the liquid crystal polymer diaphragm. The preparation method comprises the following steps: providing a soluble liquid crystal polymer, dissolving the soluble liquid crystal polymer in a first solvent, stirring and mixing to obtain a first mixed solution. Fillers are added into the first mixed solution, and dispersion treatment and defoaming treatment are performed to obtain a slurry. The fillers comprise at least one of paraffin oil, aluminum triacetylacetone powder, azodicarbonamide, calcium carbonate powder, silica powder, sodium bicarbonate powder and starch powder. A substrate is provided, the slurry is coated on the substrate, and a wet film is formed on the substrate. The wet film is subjected to drying and curing treatment, and the fillers are removed to obtain a first film body with a porous structure. The first film body is peeled off from the substrate to obtain the liquid crystal polymer diaphragm. In the preparation process of the liquid crystal polymer diaphragm, the fillers are added, the fillers are used for occupying positions in the wet film and are removed, the porous structure in the liquid crystal polymer diaphragm is increased, and the porosity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery separator preparation technology, and in particular to a method for preparing a liquid crystal polymer separator and the liquid crystal polymer separator. Background Technology

[0002] As a key insulating component between the positive and negative electrodes in a battery, the battery separator's core function is to prevent direct contact between the electrodes, thus preventing short circuits, while allowing ions to conduct freely to ensure normal battery operation. Currently, widely used separator materials in the industry include polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), and polyimide (PI).

[0003] Liquid crystal polymers (LCPs), as special engineering plastics, possess excellent comprehensive properties. Specifically, they exhibit outstanding thermal stability (melting point >300℃, thermal decomposition temperature >400℃), high mechanical strength, good creep resistance, high voltage breakdown strength, good dimensional stability, and excellent corrosion resistance, making them a superior substrate for battery separators. However, existing LCP membrane materials have excessively strong barrier properties, making it difficult to form a porous structure, which hinders the effective conduction of electrolyte ions and limits their direct application in the field of battery separators. Summary of the Invention

[0004] This application aims to provide a method for preparing a liquid crystal polymer separator and the liquid crystal polymer separator, with the goal of increasing the porous structure of the liquid crystal polymer separator.

[0005] In a first aspect, this application proposes a method for preparing a liquid crystal polymer separator, comprising: providing a soluble liquid crystal polymer; dissolving the soluble liquid crystal polymer in a first solvent and stirring to obtain a first mixture; adding filler to the first mixture and performing dispersion and degassing treatments to obtain a slurry; the filler includes at least one selected from paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micropowder, silica micropowder, sodium bicarbonate micropowder, and starch micropowder; providing a substrate; coating the slurry onto the substrate and forming a wet film on the substrate; drying and curing the wet film and removing the filler to obtain a first membrane with a porous structure; and peeling the first membrane off the substrate to obtain a liquid crystal polymer separator.

[0006] In some embodiments, the particle size of the filler is 0.1 μm to 0.8 μm; the amount of filler added is 5% to 150% of the solid content of the soluble liquid crystal polymer.

[0007] In some embodiments, the soluble liquid crystal polymer is polymerized from aromatic dicarboxylic acids, aromatic diols, and aromatic hydroxycarboxylic acids. The molar percentage of the aromatic dicarboxylic acid is 25 mol% to 49 mol%; and / or, the molar percentage of the aromatic diol is 25 mol% to 49 mol%; and / or, the molar percentage of the aromatic hydroxycarboxylic acid is 2 mol% to 50 mol%.

[0008] In some embodiments, the first solvent comprises at least one selected from N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and γ-butyrolactone. The solid content of the first mixture is 5% to 15%.

[0009] In some embodiments, the dispersion treatment includes stirring and / or dispersion disc treatment; the stirring speed of the stirring treatment is 1000 rpm to 1200 rpm, and the stirring time is 60 min to 90 min; the speed of the dispersion disc treatment is 1400 rpm to 1500 rpm. The pressure of the degassing treatment is -80 kPa to -90 kPa, and the duration of the degassing treatment is 30 min to 40 min.

[0010] In some embodiments, the drying and curing treatment of the wet film includes: placing the wet film in a first drying oven in an inert gas environment, wherein the first drying oven is heated to a first temperature at a heating rate of 0.25°C / min to 0.5°C / min, and maintained at the first temperature for a first duration; the first temperature is 130 to 170°C, and the first duration is 1 hour to 1.5 hours; the first drying oven is heated to a second temperature at a heating rate of 1.8°C / min to 2.5°C / min, and maintained at the second temperature for a second duration; the second temperature is 250°C to 320°C, and the second duration is 1 hour to 1.5 hours; the first drying oven is cooled to a third temperature at a cooling rate of 0.8°C / min to 1.2°C / min, wherein the third temperature is 50°C to 60°C.

[0011] In some embodiments, the drying and curing treatment of the wet film includes: placing the wet film in a second drying oven in an inert gas environment, wherein the second drying oven heats the film to a fourth temperature at a heating rate of 0.8°C / min to 1.2°C / min, and maintains the film at the fourth temperature for a third duration; the fourth temperature is 250°C to 320°C, and the third duration is 2 hours to 3 hours. The second drying oven then cools the film to a fifth temperature at a cooling rate of 0.8°C / min to 1.2°C / min, wherein the fifth temperature is 50°C to 60°C.

[0012] In some embodiments, the drying and curing treatment of the wet film and the removal of the filler includes: removing the filler by a physical removal method during the drying and curing process, the physical removal method including at least one of volatilization, evaporation, and vaporization; and / or, after the wet film is dried and cured, an intermediate film is obtained; the intermediate film is sprayed with an etching solution using a chemical etching method, and the filler is removed after standing, cleaning, and drying.

[0013] In some embodiments, the thickness of the wet film is 300 μm to 800 μm.

[0014] Secondly, this application also provides a liquid crystal polymer separator, which is prepared by the liquid crystal polymer separator preparation method as described in any one of the first aspects, wherein the liquid crystal polymer separator includes a plurality of pores distributed in the interior and surface of the liquid crystal polymer separator; and the thickness of the liquid crystal polymer separator is 5 μm to 50 μm.

[0015] Unlike existing technologies, this application provides a method for preparing a liquid crystal polymer separator, comprising: providing a soluble liquid crystal polymer; dissolving the soluble liquid crystal polymer in a first solvent and stirring to obtain a first mixture; adding filler to the first mixture and performing dispersion and degassing treatments to obtain a slurry; the filler includes at least one selected from paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micropowder, silica micropowder, sodium bicarbonate micropowder, and starch micropowder; providing a substrate; coating the slurry onto the substrate and forming a wet film on the substrate; drying and curing the wet film and removing the filler to obtain a first membrane with a porous structure; and peeling the first membrane off the substrate to obtain a liquid crystal polymer separator. This application, by adding filler during the preparation of the liquid crystal polymer separator and utilizing the filler's occupancy in the wet film and subsequent removal, constructs an interconnected or independently distributed porous structure in the liquid crystal polymer matrix, thereby increasing the porosity of the liquid crystal polymer separator. This porous structure can provide transport channels for charge carriers such as lithium ions, thereby improving the ionic conductivity of the liquid crystal polymer separator. Meanwhile, soluble liquid crystal polymers themselves have excellent mechanical properties and heat resistance. After the filler is removed, the remaining liquid crystal polymer can maintain good structural integrity and mechanical strength, reducing the phenomenon of damage to the liquid crystal polymer separator during battery assembly and charge-discharge cycles.

[0016] Additional aspects and advantages of the embodiments of this application will be described, shown, or illustrated in part by way of implementation of the embodiments of this application in the following description. Attached Figure Description

[0017] One or more embodiments are illustrated by way of example with reference to the accompanying drawings, which are not intended to limit the embodiments, and elements having the same reference numerals in the drawings are designated as similar elements.

[0018] Figure 1 This is a schematic diagram of the preparation method of the liquid crystal polymer separator according to some embodiments of this application; Figure 2 This is a schematic diagram of the structure of the liquid crystal polymer separator in some embodiments of this application; Figure 3 The following are tensile test curves for some embodiments 1 of this application.

[0019] Figure 4 The tensile test curves are for some embodiments 2 of this application.

[0020] Figure 5 Tensile test curves for some comparative examples 1 of this application. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of this application, but not all embodiments.

[0022] In this application, the reference to "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.

[0023] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0024] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0025] The technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.

[0026] Firstly, this application proposes a method for preparing a liquid crystal polymer separator, please refer to... Figure 1 The preparation method includes the following steps: Step S1: Provide a soluble liquid crystal polymer, dissolve the soluble liquid crystal polymer in a first solvent, stir and mix to obtain a first mixture.

[0027] Liquid crystal polymers are a class of polymeric materials composed of rigid rod-shaped molecular chains. Under certain conditions, these chains can spontaneously align to form a liquid crystal phase. Liquid crystal polymers possess characteristics such as heat resistance, thermal conductivity, high water resistance, and structural stability.

[0028] The soluble liquid crystal polymer is synthesized by polymerization of aromatic dicarboxylic acids, aromatic diols, and aromatic hydroxycarboxylic acids. The aromatic dicarboxylic acid comprises 25 mol% to 49 mol% of its molar percentage; and / or, the aromatic diol comprises 25 mol% to 49 mol% of its molar percentage; and / or, the aromatic hydroxycarboxylic acid comprises 2 mol% to 50 mol% of its molar percentage.

[0029] Aromatic dicarboxylic acids include terephthalic acid and 2,6-naphthalic acid. Aromatic diols include hydroquinone and bisphenol A. Aromatic hydroxycarboxylic acids include p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid. Specifically, the soluble liquid crystal polymer is polymerized by combining 32 mol% 2,6-naphthalic acid, 32 mol% hydroquinone, and 26 mol% p-hydroxybenzoic acid.

[0030] The first solvent is a polar aprotic solvent. The first solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, γ-butyrolactone, and N,N-dimethylformamide.

[0031] A homogeneous first mixture with a solid content of 5% to 15% is formed by dissolving a soluble liquid crystal polymer in a first solvent. The solid content of the first mixture can be any value from 5% to 15%, or any range between two values. For example, any value such as 5%, 7%, 9%, 11%, 13%, or 15%, or any range such as 5% to 10%, 6% to 9%, 6% to 13%, or 10% to 15%. When the solid content is controlled within the range of 5% to 15%, the first mixture has a suitable viscosity, which maintains good leveling properties, facilitating subsequent uniform coating, and reduces problems such as insufficient strength due to sagging and excessively thin film layers. Simultaneously, it can also improve defects such as coating bubbles and streaks caused by excessively high viscosity.

[0032] Preferably, the solid content of the first mixture is 8% to 10%. Within this range, the viscosity of the first mixture is easier to control, which helps reduce stress concentration caused by uneven film thickness during subsequent heat treatment, thereby improving the structural integrity and performance consistency of the liquid crystal polymer separator.

[0033] In some embodiments, dissolving the soluble liquid crystal polymer in a first solvent and stirring to obtain a first mixture includes: placing the soluble liquid crystal polymer in a first solvent with a solution temperature of 120°C to 160°C, stirring in an oxygen-free environment at a stirring intensity of 500 N / m. 3 Up to 2000 N / m 3 The dissolution time is 1 to 4 hours to ensure that the first mixture is evenly mixed.

[0034] Step S2: Add filler to the first mixture and perform dispersion and degassing treatment to obtain a slurry; the filler includes at least one of paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micro powder, silica micro powder, sodium bicarbonate micro powder, and starch micro powder.

[0035] Fillers are pore-forming agents used to create porous structures inside and on the surface of liquid crystal polymer separators. Specifically, the selected fillers must have the property of being effectively removed during or after the drying and curing process to leave the desired porous structure.

[0036] Paraffin oil is a mixture of liquid hydrocarbons. It is a transparent oily liquid at room temperature and has good fluidity and chemical stability. Its boiling point is usually above 300℃. During the high-temperature stage of drying and curing, it can be removed from the wet film by evaporation or vaporization, thus leaving corresponding pores in the liquid crystal polymer matrix.

[0037] Aluminum triacetylacetonate powder is an organometallic complex that appears as a white crystalline powder. It has a low decomposition temperature. During the drying and curing process, when the temperature rises to its decomposition point (usually between 200°C and 300°C), a decomposition reaction occurs, producing gas and forming volatile products, which then escape from the wet film, leaving pores.

[0038] Azodicarbonamide is a commonly used chemical foaming agent. When heated, it decomposes to release gases such as nitrogen, carbon monoxide, and carbon dioxide. These gases expand inside the wet film to form bubbles. After drying and curing, the bubbles escape to form a porous structure.

[0039] Calcium carbonate micropowder and silica micropowder are inorganic fillers with relatively stable chemical properties. After drying and curing, they are typically removed using chemical etching methods, such as spraying the intermediate film with dilute hydrochloric acid. Calcium carbonate micropowder reacts with dilute hydrochloric acid to produce soluble calcium chloride, carbon dioxide, and water. Silica micropowder can be removed by etching with hydrofluoric acid, thereby creating pores in the liquid crystal polymer separator.

[0040] Sodium bicarbonate micro powder decomposes to produce carbon dioxide gas when heated, which can be used as a physical foaming filler to form pores through gas escape.

[0041] Starch powder, as a natural organic filler, can undergo carbonization and decomposition at high temperatures, or be removed by washing or other methods in subsequent processing, thus forming pores.

[0042] By adding fillers and utilizing their occupancy in the wet film and subsequent removal, interconnected or independently distributed porous structures are constructed within the liquid crystal polymer matrix. This increases the porosity of the liquid crystal polymer separator. This porous structure provides transport channels for charge carriers such as lithium ions, thereby improving the ionic conductivity of the liquid crystal polymer separator.

[0043] It should be noted that in actual production, the porosity, pore size, and distribution of the liquid crystal polymer separator can be flexibly controlled by selecting different types and combinations of fillers to meet the differentiated requirements of different battery systems for the ion conduction performance of the separator. For example, by mixing paraffin oil with calcium carbonate micropowder, the paraffin oil evaporates at high temperature to form larger interconnected pores, while the calcium carbonate micropowder is etched to form smaller dispersed pores, thus forming a composite pore structure and improving the ion conduction performance of the liquid crystal polymer separator. Incompletely decomposed fillers form a certain supporting structure in the polymer separator, thereby improving the mechanical strength of the polymer separator.

[0044] In some embodiments, the particle size of the filler is from 0.1 μm to 0.8 μm. The particle size can be any value from 0.1 μm to 0.8 μm, or a range between any two values. For example, any value such as 0.1 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.7 μm, or 0.8 μm, or any range such as 0.1 μm to 0.3 μm, 0.2 μm to 0.5 μm, 0.4 μm to 0.7 μm, or 0.6 μm to 0.8 μm, can be selected. Controlling the particle size of the filler within the range of 0.1 μm to 0.8 μm is beneficial for the uniform dispersion of the filler in the first mixture, reducing agglomeration and minimizing the phenomenon of localized pore concentration or excessive size caused by agglomeration of large-diameter filler particles, which affects the mechanical properties of the liquid crystal polymer separator. Furthermore, the pore size formed after removal of the filler within this particle size range provides good ion conduction channels, reducing the penetration of active material particles from the positive and negative electrodes of the battery and lowering the risk of short circuits.

[0045] In some embodiments, the amount of filler added is 5% to 150% of the solid content of the soluble liquid crystal polymer. The amount of filler added can be any value from 5% to 150%, or any range between two values. For example, any value such as 5%, 10%, 20%, 30%, 50%, 80%, 100%, 120%, or 150%, or any range such as 5% to 20%, 10% to 30%, 20% to 50%, 50% to 100%, or 80% to 150%. Controlling the amount of filler added within the range of 5% to 150% allows for the formation of a certain number of porous structures on the liquid crystal polymer separator, while also ensuring that the liquid crystal polymer separator possesses certain mechanical strength and structural stability.

[0046] Preferably, the filler content is 10% to 100% of the soluble liquid crystal polymer solid content. This filler content range achieves a better balance between the porosity and mechanical strength of the liquid crystal polymer membrane. For example, when the filler content is 10% to 50%, a suitable porous structure is formed to meet basic ion conduction requirements, while the liquid crystal polymer membrane exhibits high mechanical strength. When the filler content is 60% to 100%, the increased number of pores helps to further improve ionic conductivity while maintaining a certain level of mechanical strength, reducing the risk of structural damage.

[0047] Dispersion treatment refers to the process of adding the filler to the first mixture according to the above-mentioned addition amount, and then using specific dispersion equipment and process parameters to make the filler uniformly dispersed in the first mixture.

[0048] In some embodiments, the dispersion process includes a stirring process at a speed of 1000 rpm to 1200 rpm.

[0049] In some embodiments, the dispersion process includes dispersion disc processing, wherein the dispersion disc processing speed is 1400 rpm to 1500 rpm.

[0050] In some embodiments, the dispersion processing time is 60 min to 90 min.

[0051] In some embodiments, the dispersion treatment is a combination of stirring and dispersion disc treatment. For example, stirring is first performed at a speed of 1000 rpm to 1200 rpm for 30 minutes to initially disperse the foaming agent, dispersant, and foaming aid in the first mixture. Then, dispersion disc treatment is performed at a speed of 1400 rpm to 1500 rpm for 30 to 60 minutes to further break up any small agglomerates that may exist in the first mixture through high shear force, so that the filler is uniformly dispersed in the first mixture.

[0052] Degassing treatment refers to removing air bubbles introduced into the first mixture during stirring and dispersion. This reduces the likelihood of defects such as pinholes and voids in the film layer during subsequent film formation and heat treatment, which is beneficial for improving the structural integrity and performance stability of the liquid crystal polymer separator.

[0053] In some embodiments, the degassing process employs a vacuum degassing method. Specifically, the first mixture after dispersion treatment is placed in a vacuum environment with a pressure of -80 kPa to -90 kPa for 30 to 40 minutes for degassing. Degassing reduces the bubble content in the first mixture, resulting in a smoother surface on the subsequently prepared liquid crystal polymer separator, free from pinholes or depressions caused by obvious bubbles.

[0054] Step S3: Provide a substrate, apply the slurry to the substrate, and form a wet film on the substrate.

[0055] The substrate is a support used to carry the slurry and give the wet film its initial shape. In this application, the substrate needs to have good chemical stability, heat resistance, and appropriate surface energy so that the slurry can be uniformly coated and separated from the cured first film.

[0056] In some embodiments, the substrate includes a glass substrate, a polytetrafluoroethylene sheet, a stainless steel foil, an aluminum foil, a copper foil, or a polyimide film, etc.

[0057] In some embodiments, the coating method includes blade coating, slot coating, dip coating, spray coating, or cast coating. For example, blade coating. The thickness of the wet film can be controlled by the gap height between the blade and the substrate.

[0058] In some embodiments, the thickness of the wet film is 300 μm to 800 μm. The thickness of the wet film can be selected within the range of 300 μm to 800 μm according to actual needs, for example, any value such as 300 μm, 400 μm, 600 μm, 800 μm, or any range such as 300 μm to 500 μm, 500 μm to 700 μm, or 600 μm to 800 μm. Controlling the thickness of the wet film within the range of 300 μm to 800 μm is beneficial for forming a liquid crystal polymer separator with a certain thickness and complete structure, and can reduce problems such as uneven curing, film cracking, or difficulty in peeling from the substrate caused by excessively thick wet films.

[0059] Preferably, the thickness of the wet film is between 15 μm and 50 μm. During the subsequent drying and curing process, the solvent evaporates more uniformly, resulting in a more uniform surface condition and a denser structure for the formed liquid crystal polymer separator.

[0060] Step S4: Dry and cure the wet membrane and remove the filler to obtain a first membrane with a porous structure.

[0061] The purpose of drying and curing the wet film is to remove the primary solvent and other volatile components that may remain in the wet film, and to promote the further orientation and solidification of the soluble liquid crystal polymer molecular chains, thereby forming a film with certain mechanical properties and structural stability.

[0062] In some embodiments, for fillers that undergo significant chemical changes, such as metal acetylacetonate salts and other thermally decomposable metal salts, for example, aluminum triacetylacetonate, copper diacetylacetonate, iron triacetylacetonate, etc., the drying and curing process of the wet film includes: placing the wet film in a first drying oven in an inert gas environment, the first drying oven being heated to a first temperature at a heating rate of 0.25°C / min to 0.5°C / min, and maintaining the first temperature at the first temperature for a first duration. The first temperature is 130 to 170°C, and the first duration is 1 hour to 1.5 hours. The first drying oven is then heated to a second temperature at a heating rate of 1.8°C / min to 2.5°C / min, and maintained at the second temperature for a second duration; the second temperature is 250°C to 320°C, and the second duration is 1 hour to 1.5 hours. The first drying oven is then cooled to a third temperature at a cooling rate of 0.8°C / min to 1.2°C / min, the third temperature being 50°C to 60°C.

[0063] In the above process, under the protection of an inert gas (such as nitrogen or argon), the temperature is increased at a rate of 0.25℃ / min to 0.5℃ / min, allowing the first solvent inside the wet film to gradually diffuse and evaporate from the inside out. This reduces the possibility of film cracking or bubble formation due to excessively rapid evaporation of the first solvent. When the temperature reaches 130 to 170℃, the first solvent (such as N-methylpyrrolidone with a boiling point of approximately 202℃ and N,N-dimethylacetamide with a boiling point of approximately 166℃) will evaporate in large quantities. After the first duration, most of the solvent can be effectively removed, allowing the wet film to initially solidify and form. When the temperature reaches the second temperature, the higher temperature of this process will continue to remove residual trace amounts of solvent, promoting further cross-linking of the soluble liquid crystal polymer molecular chains and improving the structural stability of the membrane. At the same time, for volatile fillers, such as aluminum triacetylacetonate, the second temperature is conducive to the full decomposition reaction, allowing the gases produced by decomposition to escape smoothly and form uniformly distributed pores within the wet film. During the cooling phase, the liquid crystal polymer separator gradually cools and solidifies as the temperature decreases slowly. The internal stress of the solidified first film is released, reducing the possibility of cracking or deformation caused by uneven shrinkage due to rapid cooling. At the same time, the formed pore structure can be further stabilized during the cooling process, and the strength of the pore walls gradually increases, allowing the first film to maintain its structural integrity during subsequent separation and processing.

[0064] In some embodiments, drying and curing the wet film and removing the filler includes: removing the filler during the drying and curing process. The filler is removed by physical removal methods, under temperature and / or pressure changes. For example, by at least one of volatilization, evaporation, vaporization, etc.

[0065] In some embodiments, for inorganic fillers that are chemically stable and not prone to decomposition, phase change, or chemical transformation, such as calcium carbonate micro powder or silica micro powder, the drying and curing process of the wet film includes: placing the wet film in a second drying oven in an inert gas environment, heating the second drying oven to a fourth temperature at a heating rate of 0.8°C / min to 1.2°C / min, and maintaining the fourth temperature at a third time; the fourth temperature is 250°C to 320°C, and the third time is 2 hours to 3 hours. The second drying oven then cools the film to a fifth temperature at a cooling rate of 0.8°C / min to 1.2°C / min, and the fifth temperature is 50°C to 60°C.

[0066] In the above process, due to the stable chemical properties of the filler, the main purpose of the drying and curing stage is to remove the first solvent and promote the curing of the liquid crystal polymer, without the need to decompose the filler. Raising the temperature directly to a fourth temperature of 250℃ to 320℃ and maintaining it at this temperature for 2 to 3 hours facilitates the full evaporation of the first solvent, allowing the soluble liquid crystal polymer molecular chains to fully cross-link and solidify, forming a structurally stable first film. Then, the temperature is slowly lowered to a fifth temperature of 50℃ to 60℃ at a rate of 0.8℃ / min to 1.2℃ / min. This is to reduce the cracking or deformation of the first film caused by internal stress due to rapid cooling and to maintain the structural integrity of the cured first film.

[0067] In some embodiments, drying and curing the wet film and removing the filler includes: after drying and curing the wet film, an intermediate film is obtained. The intermediate film is then chemically etched by spraying an etching solution, allowing it to stand, cleaning, and drying to remove the filler. For example, after drying and curing, for inorganic fillers that are not easily decomposed, such as calcium carbonate micropowder or silica micropowder, chemical etching is required to remove the filler and form pores. For example, the cured intermediate film is sprayed with dilute hydrochloric acid and allowed to stand for 12 hours to allow the calcium carbonate micropowder to react fully with the hydrochloric acid and be dissolved and removed. The intermediate film is then repeatedly rinsed in deionized water 3 to 5 times until the pH of the rinsing solution reaches neutral. Subsequently, the cleaned intermediate film is placed in an oven at 60°C to 80°C and dried for 2 to 3 hours to remove moisture, ultimately forming uniform pores in the liquid crystal polymer separator left by the removal of calcium carbonate micropowder.

[0068] Step S5: Peel the first membrane from the substrate to obtain the liquid crystal polymer separator.

[0069] The first film can be peeled off from the substrate by mechanical peeling or solvent-assisted peeling, and then wound up and slit to obtain a liquid crystal polymer separator.

[0070] It should be noted that when the filler is silica micropowder and the substrate is a glass substrate, hydrofluoric acid solution can be used as the etching solution. The glass substrate with the first film attached is immersed in the hydrofluoric acid solution, or sprayed with hydrofluoric acid solution. The hydrofluoric acid solution can react with the silica micropowder and chemically react with the glass substrate, promoting the formation of a porous structure in the intermediate film. Simultaneously, it gradually dissolves the glass substrate, causing the first film to separate from the substrate. After etching, the separated first film is repeatedly rinsed with deionized water to remove residual etching solution and impurities, followed by drying to finally obtain the liquid crystal polymer separator.

[0071] The method for preparing the liquid crystal polymer separator in this application is simple, controllable, and suitable for continuous production. The production process can be completed using a mature solution casting process. The pore structure can be precisely controlled by adjusting the type and proportion of fillers and process parameters, allowing for precise control of key indicators such as pore size, porosity, and thickness of the liquid crystal polymer separator, thus adapting to the needs of different types of batteries, including lithium-ion batteries and polymer batteries. The preparation method in this application is highly compatible with existing coating production lines, facilitating high-efficiency, low-cost roll-to-roll continuous manufacturing, and has a clear prospect for industrialization.

[0072] This application provides a method for preparing a liquid crystal polymer separator, comprising: providing a soluble liquid crystal polymer; dissolving the soluble liquid crystal polymer in a first solvent and stirring to obtain a first mixture; adding filler to the first mixture and performing dispersion and degassing treatment to obtain a slurry; the filler includes at least one selected from paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micro powder, silica micro powder, sodium bicarbonate micro powder, and starch micro powder; providing a substrate; coating the slurry onto the substrate and forming a wet film on the substrate; drying and curing the wet film and removing the filler to obtain a first membrane with a porous structure; and peeling the first membrane off the substrate to obtain a liquid crystal polymer separator. This application improves the porosity of the liquid crystal polymer separator by adding filler during the preparation process and utilizing the filler's occupancy in the wet film and subsequent removal to construct an interconnected or independently distributed porous structure in the liquid crystal polymer matrix. This porous structure can provide transport channels for charge carriers such as lithium ions, thereby improving the ionic conductivity of the liquid crystal polymer separator. Meanwhile, soluble liquid crystal polymers themselves have excellent mechanical properties and heat resistance. After the filler is removed, the remaining liquid crystal polymer can maintain good structural integrity and mechanical strength, reducing the phenomenon of damage to the liquid crystal polymer separator during battery assembly and charge-discharge cycles.

[0073] Secondly, embodiments of this application also provide a liquid crystal polymer separator, prepared using the liquid crystal polymer separator preparation method as described in any of the first aspects. Please refer to... Figure 2 The liquid crystal polymer separator includes several pores distributed both inside and on the surface of the liquid crystal polymer separator. The thickness of the liquid crystal polymer separator ranges from 5 μm to 50 μm.

[0074] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0075] Example 1 (1) Dissolve 100 g of liquid crystal polymer in 900 g of N-methylpyrrolidone to form a liquid crystal polymer solution with a solid content of 10%, namely the first mixture.

[0076] (2) 900g of LCP solution with a solid content of 10% and 10g of aluminum triacetylacetonate (particle size of 0.1μm) were added to a stirred tank for dispersion. The stirring speed was set to 1200 rpm, the dispersion speed was set to 1500 rpm, and the dispersion time was 30 min. After dispersion, the air bubbles in the first mixed solution were removed by degassing under reduced pressure. The pressure was set to -85kPa, and the degassing time was 30 min to obtain a slurry.

[0077] (3) The homogenized slurry is precisely coated on the polyimide film by casting to obtain a wet film. The thickness of the wet film is adjusted by adjusting the height of the slit between the coating blade and the polyimide film. The thickness of the wet film is 25 μm.

[0078] (4) The wet film was placed in an oven to dry and cure. Under nitrogen protection, the temperature was increased to 150°C at a heating rate of 0.25°C / min and held for 1 hour. Then the temperature was increased to 280°C at a heating rate of 2°C / min and held for 1 hour. Then the temperature was decreased to 60°C at a cooling rate of 1°C / min to obtain the first film.

[0079] (5) The polyimide film is peeled off by an automatic film peeling machine, so that the first film body is separated from the polyimide film and a liquid crystal polymer separator is obtained.

[0080] Example 2 (1) Dissolve 100 g of liquid crystal polymer in 900 g of N-methylpyrrolidone to form a liquid crystal polymer solution with a solid content of 10%, namely the first mixture.

[0081] (2) 1000g of LCP solution with a solid content of 10% and 100g of calcium carbonate micropowder (particle size of 0.8μm) were added to a stirred tank for dispersion. The stirring speed was set to 1200 rpm, the dispersion speed was set to 1500 rpm, and the dispersion time was 60 min. After dispersion, the air bubbles in the first mixed solution were removed by degassing under reduced pressure. The pressure was set to -85kPa, and the degassing time was 30 min to obtain a slurry.

[0082] (3) The homogenized slurry is precisely coated on the copper foil by casting to obtain a wet film. The thickness of the wet film is adjusted by adjusting the height of the slit between the coating blade and the copper foil. The thickness of the wet film is 25 μm.

[0083] (4) The wet film is placed in an oven to dry and cure. Under nitrogen protection, the temperature is increased to 280°C at a heating rate of 1°C / min and held for 2 hours. Then the temperature is decreased to 60°C at a cooling rate of 1°C / min to obtain the intermediate film.

[0084] (5) Fix the intermediate membrane and spray it with acidic copper etching solution (main components: dilute hydrochloric acid, copper chloride) for 30 minutes. After spraying, let the intermediate membrane stand for 12 hours to remove copper foil and calcium carbonate. Then, wash the intermediate membrane in deionized water until the pH of the rinsing solution is neutral. After washing, place the intermediate membrane in a vacuum drying oven at 65°C and dry it under a vacuum of -0.09 MPa for 2.5 hours to obtain the liquid crystal polymer separator.

[0085] Comparative Example 1 (1) Dissolve 100 g of liquid crystal polymer in 900 g of N-methylpyrrolidone to form a liquid crystal polymer solution with a solid content of 10%, namely the first mixture.

[0086] (2) 1000g of the first mixture is precisely coated on the copper foil by casting to obtain a wet film. The thickness of the wet film is adjusted by adjusting the height of the slit between the coating blade and the copper foil. The thickness of the wet film is 25μm.

[0087] (3) The wet film is placed in an oven to dry and cure. Under nitrogen protection, the temperature is increased to 280°C at a heating rate of 1°C / min and held for 2 hours. Then the temperature is decreased to 60°C at a cooling rate of 1°C / min to obtain the intermediate film.

[0088] (4) Fix the intermediate membrane and spray it with an acidic copper etching solution (main components: dilute hydrochloric acid and copper chloride) for 30 minutes. After spraying, let the intermediate membrane stand for 12 hours to remove the copper foil. Then, wash the intermediate membrane in deionized water until the pH of the rinsing solution is neutral. After washing, place the intermediate membrane in a vacuum drying oven at 65°C and dry it under a vacuum of -0.09 MPa for 2.5 hours to obtain the liquid crystal polymer separator.

[0089] The liquid crystal polymer separators prepared in Example 1, Example 2 and Comparative Example 1 were tested as follows.

[0090] Tensile strength test: The tensile strength of the liquid crystal polymer separator was tested according to GB / T 1040.3-2006 "Test for Tensile Properties of Plastics" and ASTM D882-10 "Standard Test Method for Tensile Properties of Thin Plastic Sheeting". Three sets of data were obtained for both the example and comparative examples. The samples were cut into dumbbell shapes with a cutter, and the tensile strength and elongation at break were measured. The testing equipment was a C45.102 electronic universal testing machine manufactured by Xin Sansi Company. The tensile testing machine was used to stretch the sample at a speed of 10 mm / min, and the tensile strength at fracture was determined.

[0091] Heat shrinkage rate test: The heat shrinkage rate of the liquid crystal polymer separator was tested according to GB / T 13519-2016 "Polyethylene Heat Shrinkable Film for Packaging" and ASTM D 2732-08 "Standard Test Method for Unrestrained Linear Thermal Shrinkage of Plastic Film and Sheeting". Three sets of data were tested for both the example and comparative examples. The samples were cut into 100mm × 100mm squares and placed at 90℃ for 90 min. After removal, the dimensions of the samples were measured. The heat shrinkage rate of the samples is the percentage of the shrinkage value of the liquid crystal polymer separator area to the original area.

[0092] Thermal deformation temperature testing: Following NASA TM 2010-216099 standard, thermomechanical analysis (TMA) was used to determine the melting point, shrinkage initiation temperature, and deformation temperature of the samples. The testing equipment was a PerkinElmer TMA4000. Samples were cut into rectangles approximately 10 mm long and 3 mm wide and fixed in a film tension fixture. During testing, the parameters were set to a load of 0.02 N and a heating rate of 5 °C / min until the temperature exceeded the material's melting point, causing the tension to cause the film to rupture.

[0093] Liquid absorption rate test: The liquid absorption rate of the liquid crystal polymer separator was tested according to QB / T 2303.11-2008 "Battery Pulp Paper Part 11: Determination of Liquid Absorption Rate". Three sets of data were tested for both the example and comparative examples. The sample was cut into 20mm×20mm squares, and the sample mass was measured. Then, it was immersed in 1 mol / L LiPF6 / EC+DMC+EMC (ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1) for 60 min. After removal, the electrolyte on the sample surface was absorbed with filter paper, and the mass of the liquid crystal polymer separator after immersion was measured. The liquid absorption rate of the sample is the percentage of the mass difference of the separator before and after immersion to the initial mass.

[0094] Dielectric constant testing: The dielectric constant of the liquid crystal polymer separator samples was determined using the resonant cavity method according to the IPC-TM-650 standard. Three sets of data were tested for both the example and comparative examples. Samples were cut into 80mm × 80mm squares, dried in an oven at 60°C for 2 hours, and then equilibrated at 25°C and 50%RH for 24 hours. The testing equipment consisted of a Keysight E5071 network analyzer and a discrete dielectric resonator SPDR fixture. The test frequency was 10 GHz, the test temperature was 25°C, and the ambient humidity was 50%RH.

[0095] Porosity Testing: Following GB / T 2679.3-1996 "Determination of Maximum Pore Size of Filter Paper and Paperboard" and ASTM F316-03 "Standard Test Method for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test", the porosity of the liquid crystal polymer membrane was determined using a combination of bubble point and airflow methods. Three sets of data were tested for both the example and comparative examples. Samples were cut into 47mm diameter circles and installed in a dedicated test fixture. The membrane was first completely immersed in anhydrous ethanol to remove air from the pores. Then, it was connected to a pore size / porosity measuring instrument (such as a PMI Porometer 3G), and the gas pressure was gradually increased, recording the flow rate change as the gas passed through the membrane. The maximum pore size was calculated based on the bubble point pressure, and the average pore size was calculated using the integrated flow rate curve. Based on the dry-wet flow rate difference and parameters such as membrane thickness and density, the percentage of the total pore volume to the total membrane volume was calculated, i.e., the porosity. Porosity Results: The results of the tensile strength test are shown in Table 1 and Figures 3 to 5 As shown.

[0096] Table 1

[0097] Figures 3 to 5In Table 1, the tensile test curves for Examples 1, 2, and Comparative Example 1 are all provided. The horizontal axis represents displacement (mm), and the vertical axis represents force (N). According to Table 1, the average tensile strength of the liquid crystal polymer separator prepared in Comparative Example 1 is 181.38 MPa, the average tensile strength of Example 1 is 162.73 MPa, and the average tensile strength of Example 2 is 150.64 MPa. Compared to Comparative Example 1 without filler, the tensile strength of the liquid crystal polymer separators prepared in Examples 1 and 2 with filler is slightly lower. However, the tensile strength of Examples 1 and 2 remains at a high level, sufficient to meet the physical stress requirements of the battery separator during assembly and use, such as compression and expansion.

[0098] The results of the heat shrinkage rate test are shown in Table 2.

[0099] Table 2

[0100] As shown in Table 2, the average thermal shrinkage rate of the liquid crystal polymer separator prepared in Comparative Example 1 was 0.07%, the average thermal shrinkage rate of Example 1 was 0.12%, and the average thermal shrinkage rate of Example 2 was 0.17%. Compared with Comparative Example 1, the thermal shrinkage rates of Examples 1 and 2 increased slightly, but remained at extremely low levels overall. This indicates that even after introducing a porous structure, the liquid crystal polymer separator still maintains the excellent thermal stability inherent in the liquid crystal polymer material, effectively suppressing the separator shrinkage problem that may occur due to temperature rise during battery operation, thereby reducing the risk of internal short circuits in the battery.

[0101] The results of the heat deformation temperature test are shown in Table 3.

[0102] Table 3

[0103] Table 3 shows that the initial shrinkage temperature of the liquid crystal polymer separator prepared in Comparative Example 1 is 152℃, the deformation temperature is 177℃, and the rupture temperature is 287℃. The initial shrinkage temperature of Example 1 is 156℃, the deformation temperature is 172℃, and the rupture temperature is 281℃. The initial shrinkage temperature of Example 2 is 153℃, the deformation temperature is 169℃, and the rupture temperature is 273℃. It can be seen that the deformation temperature difference between the liquid crystal polymer separators in the examples and those in Comparative Example 1 is small, with initial shrinkage temperatures all greater than 150℃ and melting rupture temperatures all greater than 250℃. This indicates that although the liquid crystal polymer separator prepared in this application has slight differences in deformation and rupture characteristics at high temperatures compared to the pure liquid crystal polymer separator, it still maintains good high-temperature resistance and can maintain structural stability under the high operating temperature environment that the battery may encounter, making it less prone to premature shrinkage, deformation, or even rupture, thereby ensuring the safe operation of the battery.

[0104] The results of the liquid absorption rate test are shown in Table 4.

[0105] Table 4

[0106] As shown in Table 4, the average liquid absorption rate of the liquid crystal polymer membrane prepared in Comparative Example 1 was only 0.42%, while the liquid absorption rate of Example 1 was 20.49% and that of Example 2 was 29.27%. This indicates that by introducing specific fillers (such as calcium carbonate micropowder in Example 2) into the liquid crystal polymer matrix and subsequently processing them to form a porous structure, the absorption capacity of the liquid crystal polymer membrane for electrolyte can be improved, thus meeting the requirements for ion conduction in the electrolyte.

[0107] The results of the dielectric constant test are shown in Table 5.

[0108] Table 5

[0109] As shown in Table 5, the average dielectric constant of the liquid crystal polymer separator prepared in Comparative Example 1 is 3.23, the average dielectric constant of Example 1 is 2.79, and the average dielectric constant of Example 2 is 2.01. Compared with Comparative Example 1 without filler, the dielectric constants of the liquid crystal polymer separators prepared in Examples 1 and 2 are significantly lower. A lower dielectric constant helps to reduce dielectric losses inside the battery, reduce energy loss during transmission, and improve the charge-discharge efficiency and cycle performance of the battery.

[0110] The porosity test results are shown in Table 6.

[0111] Table 6

[0112] Table 6 shows that the average porosity of the liquid crystal polymer membrane prepared in Comparative Example 1 was 4.63%, the average porosity of Example 1 was 48.9%, and the average porosity of Example 2 was 54.7%. This indicates that adding removable fillers to the liquid crystal polymer solution can significantly improve the porosity of the liquid crystal polymer membrane. High porosity provides ample channels for electrolyte storage and ion transport, which is beneficial for improving ionic conductivity and thus improving the rate performance and charge / discharge efficiency of the battery.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them; under the concept of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of this application as described above, which are not provided in detail for the sake of brevity; although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for preparing a liquid crystal polymer separator, characterized in that, include: A soluble liquid crystal polymer is provided, and the soluble liquid crystal polymer is dissolved in a first solvent and stirred to obtain a first mixture. A filler is added to the first mixture, and dispersion and degassing treatments are performed to obtain a slurry; the filler includes at least one of paraffin oil, aluminum triacetylacetonate powder, azodicarbonamide, calcium carbonate micro powder, silica micro powder, sodium bicarbonate micro powder, and starch micro powder. Provide a substrate, apply the slurry to the substrate, and form a wet film on the substrate; The wet membrane is dried and cured, and the filler is removed to obtain a first membrane with a porous structure. The first film is peeled off from the substrate to obtain a liquid crystal polymer separator.

2. The preparation method according to claim 1, characterized in that, The filler has a particle size of 0.1 μm to 0.8 μm; the amount of filler added is 5% to 150% of the solid content of the soluble liquid crystal polymer.

3. The preparation method according to claim 1, characterized in that, The soluble liquid crystal polymer is formed by polymerization of aromatic dicarboxylic acids, aromatic diols, and aromatic hydroxycarboxylic acids; The aromatic dicarboxylic acid has a molar percentage of 25 mol% to 49 mol%; and / or, the aromatic diol has a molar percentage of 25 mol% to 49 mol%; and / or, the aromatic hydroxycarboxylic acid has a molar percentage of 2 mol% to 50 mol%.

4. The preparation method according to claim 1, characterized in that, The first solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and γ-butyrolactone; The solid content of the first mixture is 5% to 15%.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The dispersion treatment includes stirring and / or dispersing disc treatment; the stirring speed of the stirring treatment is 1000 rpm to 1200 rpm, and the stirring time is 60 min to 90 min; the speed of the dispersing disc treatment is 1400 rpm to 1500 rpm. The degassing treatment is performed at a pressure of -80 kPa to -90 kPa and for a duration of 30 min to 40 min.

6. The preparation method according to any one of claims 1 to 4, characterized in that, The drying and curing process of the wet film includes: In an inert gas environment, the wet film is placed in a first drying oven, which heats to a first temperature at a rate of 0.25°C / min to 0.5°C / min and maintains the temperature at the first temperature for a first duration; the first temperature is 130 to 170°C and the first duration is 1 hour to 1.5 hours. The first drying oven is heated to a second temperature at a heating rate of 1.8℃ / min to 2.5℃ / min, and held at the second temperature for a second duration; the second temperature is 250℃ to 320℃, and the second duration is 1h to 1.5h. The first drying oven cools down to a third temperature at a rate of 0.8℃ / min to 1.2℃ / min, wherein the third temperature is 50℃ to 60℃.

7. The preparation method according to any one of claims 1 to 4, characterized in that, The drying and curing process of the wet film includes: In an inert gas environment, the wet film is placed in a second drying oven, which is heated to a fourth temperature at a rate of 0.8°C / min to 1.2°C / min, and maintained at the fourth temperature for a third duration; the fourth temperature is 250°C to 320°C, and the third duration is 2h to 3h. The second drying oven cools down to the fifth temperature at a rate of 0.8℃ / min to 1.2℃ / min, where the fifth temperature is 50℃ to 60℃.

8. The preparation method according to any one of claims 1 to 4, characterized in that, The process of drying and curing the wet film and removing the filler includes: During the drying and curing process, the filler is removed by a physical removal method, which includes at least one of volatilization, evaporation, and vaporization; and / or, After the wet film is dried and cured, an intermediate film is obtained; the intermediate film is sprayed with etching solution using a chemical etching method, and after standing, cleaning, and drying, the filler is removed.

9. The preparation method according to claim 1, characterized in that, The thickness of the wet film is 300 μm to 800 μm.

10. A liquid crystal polymer separator, characterized in that, The liquid crystal polymer separator is prepared by the preparation method of any one of claims 1 to 9, wherein the liquid crystal polymer separator includes a plurality of pores distributed in the interior and surface of the liquid crystal polymer separator; and the thickness of the liquid crystal polymer separator is 5 μm to 50 μm.